EFEK TERAPI AKUPUNTUR UNTUK PASIEN TRIGGER FINGER - Justin Elyoenai; Suryawan Ang (Jurnal Cakrawala Ilmiah, 2025)
Background: Trigger finger (stenosing tenosynovitis) is a musculoskeletal disorder caused by inflammation of the flexor tendon, leading to pain and limited finger movement. Acupuncture is increasingly being researched as an alternative therapy due to its potential in alleviating these symptoms. Objective: This study aims to analyze recent research on the effects of acupuncture on trigger finger, including the acupuncture points used, therapy parameters, and clinical outcomes. Methods: This study employs a systematic literature review approach with descriptive qualitative methods on journals from the last 10 years discussing the use of acupuncture (manual, electrical, or laser) for trigger finger. Results: The majority of studies report that acupuncture at the Ashi/A1 pulley point, LI4 (Hegu), SI3 (Houxi), SJ5 (Waiguan), and PC6 (Neiguan) significantly improves pain, stiffness, and hand function, especially after 4–12 therapy sessions.